PENGARUH PERUNDUNGAN TERHADAP GANGGUAN PSIKOLOGIS BAGI MAHASISWA - Fadiah, Denaya Ayu; Afifah, Nazwa Nur; Fadillah, Rida Nurul; Effendi, Ridwan; Fitria, Ratna (Jendela Inovasi Daerah, 2023)
Bullying is an act of violence that can cause psychological disorders in someone. Bullying can be done with the aim of hurting someone either verbally, physically or through social media. Currently cases of bullying are rife among students in Indonesia. The impact experienced by victims of bullying can lead to disturbed psychological conditions and physical health complaints. Therefore, this article was created with the aim of adding a sense of social awareness to cases of bullying in the surrounding environment, implementing Pancasila values in actions and behavior, and educating both victims and perpetrators of bullying. The method used in this study is qualitative which is distributed through questionnaires to university students. The results of the study show that among adolescents, especially college students, cases of bullying are still very high, victims of acts of bullying will experience psychological pressure which affects the mental health of victims. This condition can cause high levels of anxiety, depression and decreased morale of victims. Pancasila values should be implemented by all Indonesian people, especially students, especially in the second precept which reads "Kemanusiaan yang adil dan beradab" which relates to cases of bullying, and socialization of cases of bullying is one of the efforts to prevent cases of bullying.